Non-HDL or LDL cholesterol in heterozygous familial hypercholesterolaemia: findings of the Simon Broome Register. Issue 4 (August 2020) - Soran, Handrean; Cooper, Jackie A.; Durrington, Paul N.; Capps, Nigel; McDowell, Ian F.W.; Humphries, Steve E.; Neil, Andrew
Abstract : Purpose of review: The role of non-HDL-C in the identification and management of lipid disorders is not clearly defined, although UK guidelines recommend its wider use in assessing the need for lipid-lowering therapy and as a treatment target. Recent findings: We examined the implications of the use of non-HDL-C as opposed to LDL-C in 253 people with hypercholesterolaemia before treatment and 573 after treatment in whom fasting total serum cholesterol, HDL-C and LDL-C had been recorded and the diagnosis of heterozygous familial hypercholesterolemia (heFH) was investigated by genetic testing. The difference and the limits of agreement between non-HDL-C and LDL-C calculated using the Friedewald formula were assessed in those with and without heFH-causing mutations. Summary: There were 147 mutation-positive and 106 mutation-negative pretreatment participants and 395 mutation-positive and 178 mutation-negative patients receiving treatment. The difference between non-HDL-C and LDL-C pretreatment in mutation-positive people (mean LDL-C 7.73 mmol/l) was 0.67 mmol/l (95% CI 0.62–0.73) and posttreatment (mean LDL-C 4.71 mmol/l) was 0.62 mmol/l (95% CI 0.59–0.65) with wide limits of agreement of −0.02 to 1.37 and 0.07–1.18 mmol/l, respectively. Among patients with heterozygous familial hypercholesterolaemia, use of estimated LDL-C derived from non-HDL-C in place of calculated LDL-C may result in diagnostic misclassification and difficulty in assessing the true reduction in LDL-C with treatment, because of the wide inter-individual limits of agreement around the mean difference between non-HDL-C and LDL-C.